Health-related quality of life of perinatally HIV-infected young people: a longitudinal study. Issue 2 (1st February 2022) - ter Haar, A. M.; Van den Hof, M.; Scherpbier, H. J.; Oostrom, K. J.; Haverman, L.; Pajkrt, D.
ABSTRACT: Young people perinatally infected with HIV (pHIV) are at risk of a lowered health-related quality of life (HRQOL). Previous evaluation of the NeurOlogical, VIsual and Cognitive performance in HIV-infected Children (NOVICE)-cohort showed no difference in HRQOL between pHIV and matched HIV-uninfected controls (HIV-), yet a higher percentage of pHIV had impaired HRQOL. The aim of this study is to compare the change over time in HRQOL of pHIV to HIV- over a 5-year period. We used the Pediatric Quality of Life Inventory (PedsQL)™ 4.0 to repeat HRQOL assessment. High PedsQL scores indicate good HRQOL. Fifteen/33 (45.5%) pHIV and 17/37 (45.9%) HIV- completed both assessments. At the first assessment, the mean age was 13.1 years (range 8.0–18.4). PHIV scored higher than HIV- on Emotional functioning and on Total scale score. After five years, the mean age was 17.6 years (range 12.1–22.8). PHIV scored higher than HIV- on all scales, except Social functioning. PHIV did not differ significantly from the Dutch norm on either time-point. LMEM showed no difference in change over time for any of the PedsQL scales. In this study, young people with pHIV receiving high-quality health care, including monitoring of HRQOL, remain to experience a good HRQOL.